Кодування сигналів у мобільному зв’язку на основі поліномів Чебишева - Цьова, О. В. (ХНУРЭ, 2009)
The given work is devoted to the discrete cosine transform. Discrete cosine transform are important to numerous applications in science and engineering, from lossy compression of audio and images to spectral methods for the numerical solution of partial differential equations
Keywords: Кодування сигналів; поліном Чебишева